2006
DOI: 10.1113/jphysiol.2006.110791
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor affects Ca2+ currents via the p75 receptor to enhance prolactin mRNA levels in GH3 rat pituitary cells

Abstract: In clonal pituitary GH 3 cells, spontaneous action potentials drive the opening of Ca v 1 (L-type) channels, leading to Ca 2+ transients that are coupled to prolactin gene transcription. Nerve growth factor (NGF) has been shown to stimulate prolactin synthesis by GH 3 cells, but the underlying mechanisms are unknown. Here we studied whether NGF influences prolactin gene expression and Ca 2+ currents. By using RT-PCR, NGF (50 ng ml −1 ) was found to augment prolactin mRNA levels by ∼80% when applied to GH 3 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Hence, it has been reported that chronic treatment with agonists of the dopaminergic D2 receptors down-regulate HVA Ca 2+ channel expression, leading to a reduction in Ca 2+ current and secretory activity in cultured melanotropes (Cota and Hiriart 1989;Chronwall et al 1995;Fass et al 1999). On the other hand, chronic treatment with epidermal growth factor has been shown either to increase (Meza et al 1994), or decrease (Fu et al 1997) HVA Ca 2+ current density, while nerve growth factor (Lopez- Dominguez et al 2006) or glucocorticoid hormones (Fomina et al 1993(Fomina et al , 1996 significantly enhance HVA current density in clonal pituitary cells.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, it has been reported that chronic treatment with agonists of the dopaminergic D2 receptors down-regulate HVA Ca 2+ channel expression, leading to a reduction in Ca 2+ current and secretory activity in cultured melanotropes (Cota and Hiriart 1989;Chronwall et al 1995;Fass et al 1999). On the other hand, chronic treatment with epidermal growth factor has been shown either to increase (Meza et al 1994), or decrease (Fu et al 1997) HVA Ca 2+ current density, while nerve growth factor (Lopez- Dominguez et al 2006) or glucocorticoid hormones (Fomina et al 1993(Fomina et al , 1996 significantly enhance HVA current density in clonal pituitary cells.…”
Section: Discussionmentioning
confidence: 97%
“…When OHCs were treated with NGF together with k252a, NGF-induced neuronal activity increment still occurred, but the sustained LTP-like effect after wash-out no longer occurred. Previously, k252a was reported to suppressed LTP induction and synaptic activity [15,16]. Our results demonstrate that k252a may block the NGF-mediated LTP-like effect.…”
Section: Discussionmentioning
confidence: 52%
“…Likewise, it is well established that the expression levels of LVA channels can be subjected to long-term regulation by different extracellular chemical messengers, including 17b-oestradiol, insulin, neural growth factor, transforming growth factor-b1, and bone morphogenetic protein-2 (Ritchie 1993;Meza et al 1994;Avila et al 2006;López-Domínguez et al 2006). Of particular interest is that chronic treatment with GCs decreases LVA current density in GH 3 cells (Meza et al 1994).…”
Section: Discussionmentioning
confidence: 98%